Decarbonisation and renewable energies in Hungary - Nagy, Orsolya (Acta Agraria Debreceniensis, 2014)
The decarbonisation of the power sector signifies reducing its carbon dependency. The aim of several programmes is making a conversion to a sustainable & low-carbon economy. Some of the targets by the EU are legally binding, thus appear in the national legislation and strategies. To meet the objective, we need to use renewable energy soures expansively.